Skin, muscles, and bones - Parker, Steve (Milwaukee, WI : Gareth Stevens Pub., 2005)
Presents an overview of human skin, muscles, and bones, provides information about how they work together, discusses related illnesses and diseases, and includes photographs, fact boxes, and suggested activities and experiments.
Includes index.
Library Media Connection.
School Library Journal.
Wilson's Junior High School.
7.1
5-8
Keywords: Musculoskeletal system -- Juvenile literature; Skin -- Juvenile literature; Muscular system; Skin; Musculoskeletal system; Skin